P203 Oral omeprazole and diclofenac intake is associated with increased faecal calprotectin levels: a randomised open-label clinical trial. (30th January 2023) - Rendek, Z; Falk, M; Grodzinsky, E; Kechagias, S; Hjortswang, H
Abstract: Background: Non-steroidal anti-inflammatory drugs and proton pump inhibitors are known to affect the diagnostics of gastrointestinal disorders. The aim of this study was to investigate to what extent omeprazole, diclofenac or co-administration of these affects faecal calprotectin (FC) levels, and the normalisation interval after cessation. Methods: Participants received 20 mg omeprazole daily for two weeks in the first sequence, 50 mg oral diclofenac three times daily for two weeks in the second and co-administration of these for two weeks in the third, with washout periods in between. The first two sequences were randomised to a different order. FC was measured on day 0, 4, 7, 14, 21, 28 and 35 and thereafter at 7-day intervals until normalisation in each sequence. Results: Thirty-two healthy volunteers were included. During drug intake, 39% on diclofenac (median 70.8 µg/g; range 50.2-1080 µg/g), 53% on omeprazole (median 85.3 µg/g; range 51.1-249 µg/g) and 69% on omeprazole + diclofenac (median 101.5 µg/g; range 51.5-532 µg/g) had FC levels above normal. In the diclofenac sequence, FC returned to normal in all participants within two weeks of cessation and in the omeprazole and co-administration sequences, within three weeks of cessation. No statistical significant difference was found with respect to drug order. Conclusion: Short-term intake of omeprazole, diclofenac or co-administration appears to increase FC levels. In patients with increased FC on omeprazole alone or in combination with diclofenac, a repeated FC test is recommended at least three weeks after cessation. On diclofenac alone, it is sufficient to repeat the FC test two weeks after cessation.